La relación del estrés y el desempeño académico en estudiantes de educación superior durante el COVID-19 - Anaya Almeida, María Fernanda (2022)
The Covid-19 pandemic has brought with it circumstances that have placed higher education students in stressful situations in the last two years, which has contributed to affecting academic performance. Therefore, this study aimed to identify the relationship between stress and academic performance in higher education students during Covid-19. To achieve this, a systematic search was conducted following the PRISMA indications (Page et al., 2021) within the EBSCOhost, Web of Science and Scopus databases and ten investigations that met the inclusion and exclusion criteria were analyzed. The results showed that the higher the level of stress in the students, the lower the academic performance. Some of the factors involved in this relationship are the academic load, little time to entertain themselves, lack of technological knowledge, the possibility of contagion and the imbalance of work and home demands.